MODEL PENGAMBILAN KEPUTUSAN MAHASISWA MEMILIH KULIAH DI STIE EKA PRASETYA MEDAN - Muhammad Ali Akbar (Jurnal Manajemen Bisnis Eka Prasetya, 2019)
This research is to find out and analyze whether the promotional mix in the form of advertising, sales promotion, events and experiences, public relations and publicity, direct marketing, interactive marketing, word of mouth marketing, personal sales have an influence on the decision making of prospective students choosing to study at STIE Eka Prasetya , and to find out and analyze which promotional mix is ​​the most influential to be used in the context of promotional activities. This research uses a quantitative approach with a survey method. The number of samples in this study were 166 students. Data collection techniques used in this study through questionnaires and documentation studies. Advertising has a significant effect but has a negative behavior towards decision making in choosing courses at STIE Eka Prasetya. Sales promotion has a significant influence and has a positive attitude towards decision making in students choosing to study at STIE Eka Prasetya. Events and experiences have a significant influence and have a positive behavioral contribution to the decision making of students choosing to study at STIE Eka Prasetya. Public relations and publicity have a significant influence but have a negative behavioral contribution to the decision making of college students at STIE Eka Prasetya. Direct marketing has a significant influence and has a positive behavioral contribution to the decision making choosing to study at STIE Eka Prasetya. Interactive marketing has a significant influence but has a negative behavioral contribution towards the decision of students choosing to study at STIE Eka Prasetya. Word of mouth marketing has a significant influence and has a positive behavioral contribution to the decision making of students choosing to study at STIE Eka Prasetya. Personal sales have a significant influence and have a positive attitude towards the decision making of students choosing to study at STIE Eka Prasetya. The promotional mix that most influences the decision making of prospective students is Word of mouth marketing.